2017
DOI: 10.3390/molecules22071170
|View full text |Cite
|
Sign up to set email alerts
|

Development of Antimicrobial Packaging Film Made from Poly(Lactic Acid) Incorporating Titanium Dioxide and Silver Nanoparticles

Abstract: Polylactide (PLA)/nano-TiO2 and PLA/nano-TiO2/nano-Ag blends films were prepared by a solvent volatilization method. Compared to pure PLA film, the nano-blend films have low water vapor permeability (WVP) and a poor transparency. With the increase of the NPs in the PLA, the tensile strength (TS) and elastic modulus (EM) decreased, while the elongation at break (ε) increased. SEM analysis indicated a rougher cross-section of the nano-blend films. According to the FTIR analysis, no new chemical bonds were formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(85 citation statements)
references
References 51 publications
8
77
0
Order By: Relevance
“…The addition of silver nanoparticles into PLA bionanocomposites up to 1 wt.% led to increase in the intensity of main absorption bands for PLA/AgNPs 0.5 and PLA/AgNPs 1 bionanocomposites. The same effect was observed in the case of polylactide (PLA)/nano-TiO 2 and PLA/nano-TiO 2 /nano-Ag blends films obtained by solvent casting [35]. This behavior can be explained by the presence of van der Waals interactions between the HO groups of PLA and the net atomic charge on the surface of the AgNPs [23] due to the asymmetric partition of electrons.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The addition of silver nanoparticles into PLA bionanocomposites up to 1 wt.% led to increase in the intensity of main absorption bands for PLA/AgNPs 0.5 and PLA/AgNPs 1 bionanocomposites. The same effect was observed in the case of polylactide (PLA)/nano-TiO 2 and PLA/nano-TiO 2 /nano-Ag blends films obtained by solvent casting [35]. This behavior can be explained by the presence of van der Waals interactions between the HO groups of PLA and the net atomic charge on the surface of the AgNPs [23] due to the asymmetric partition of electrons.…”
Section: Discussionsupporting
confidence: 64%
“…Our results revealed an increase of the T g and the degree of crystallinity of PLA with loading of AgNPs indicated that a small amount of AgNPs acts as a nucleating agent for increase the crystallinity of the plasticized PLA [36]. Another paper stipulated that the introduction of AgNPs had no significant effect on the T g of PLA samples [30,35], while an increase in T g value was observed in the case of PLA/cassava/GRH nanoplatelets [33]. The increase in the X c was also reported in the case of PLA/chitosan foam [14].…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, it can be concluded that the incorporation of TiO 2 nanoparticles in the PLLA matrix improves its thermal stability. Similar data have been reported by Li et al , who studied the nanocomposite film obtained by the addition of 1 and 5 wt% of nano‐TiO 2 to PLA. One of the possible reasons for this behavior is that TiO 2 nanoparticles may act as a heat barrier in the early stages of thermal decomposition , as well as that the incorporation of a heat‐resistant filler into the polymer matrix causes reduction in volatile degradation products, resulting in an increase of the thermal stability of the polymer composite .…”
Section: Resultsmentioning
confidence: 99%
“…in order to prepare flexible polylactic acid)/polyethylene glycol (PLA/PEG) (1:1) film 41 . Briefly, equal amounts of PLA and PEG (500 mg) were dissolved in dichloromethane (DCM) (40 ml) and stirred at 40 °C for 30 minutes with a magnetic stirrer.…”
Section: Preparation Of Agnp Loaded Pla/peg Nanofilms Solvent Volatimentioning
confidence: 99%